Development and evaluation of a hybrid online training for panic disorder and agoraphobia - Ebenfeld, Lara (Medien- und Informationszentrum, Leuphana Universität Lüneburg, 2020)
Panic disorder is a common anxiety disorder, which is associated with high subjective burden as well as a high cost for the health economy. According to the National Treatment Guideline S3, cognitive behavior therapy is recommended as the most effective psychological treatment. However, many people in need do not have access to cognitive behavior therapy. Internet-based interventions have proven to be an effective way to provide access to evidence-based treatment to those affected. For anxiety disorders, such as panic disorder and agoraphobia, a good effectiveness of internet-based interventions has been proven in numerous international studies. However, the internet has changed over the last few years: mobile technologies have considerable potential to further improve the adherence and effectiveness of internet-based interventions. Against this background, the authors developed the hybrid online training "GET.ON Panic". In this training, an app has been integrated into a browser-based online training. The app consists of a mobile diary for self-monitoring as well as a mobile exposure-guide that supports participants in self-exposure exercises in their everyday lives.In an initial exploratory feasibility study, qualitative interview data and quantitative measurements were collected in a pre-post design of 10 participants. Usage, user friendliness, user satisfaction and acceptance of the app were generally considered high. The use of interoceptive exposure exercises and daily summaries of anxiety and mood were the most widely performed and rated the best, while in vivo exposure exercises and the monitoring of acute panic symptoms were found to be difficult.In the efficacy study, 92 participants with mild to moderate panic symptoms were randomized into two parallel groups. After eight weeks, the intervention group showed a significant improvement in the severity of panic symptoms compared to the waiting control group. Using the intention-to-treat approach, a covariance analysis with baseline values as a covariate yielded a mean effect of Cohen's d=0.66 in reducing the panic symptoms in favor of the intervention group. This effect increased to d=0.89 after three months and stayed at d=0.81 at the 6-month measurement point. Response and remission rates were also significantly higher in the intervention group. This positive effect was also shown for secondary outcomes such as depressive symptoms and quality of life. A correlation between app usage and clinical outcomes could not be found. This work was the first to demonstrate that a hybrid online training based on cognitive behavior therapy is effective in reducing panic symptoms as well as panic disorder. In addition, this work contributes to a deeper understanding of the potential of mobile technologies in the field of e-mental health.

Panikstörung ist eine verbreitete Angststörung, die mit einer hohen subjektiven Belastung sowie hohen gesundheitsökonomischen Kosten einhergeht. Gemäß der nationalen Behandelleitlinie S3 wird kognitive Verhaltenstherapie als wirksamste psychologische Behandlung empfohlen. Viele Betroffene haben jedoch keinen Zugang zur kognitiven Verhaltenstherapie. Internetbasierte Interventionen haben sich als eine wirksame Möglichkeit herausgestellt, Betroffenen Zugang zu evidenzbasierten Behandlungsmethoden zu verschaffen. Für Angsterkrankungen wie Panikstörung und Agoraphobie konnte in zahlreichen internationalen Studien eine gute Wirksamkeit von internetbasierten Interventionen nachgewiesen werden. Das Internet hat sich jedoch im Laufe der letzten Jahre gewandelt: Mobile Technologien bergen erhebliches Potenzial in sich, die Adhärenz und Wirksamkeit internetbasierter Interventionen weiter zu verbessern. Vor diesem Hintergrund haben die Autoren das hybride Online-Training „GET.ON Panik“ entwickelt. In diesem Training wurde eine App in ein browserbasiertes Online-Training integriert. Die App besteht aus einem mobilem Tagebuch zum Selbstmonitoring sowie einem mobilen Expositionsbegleiter, der Betroffene bei Selbstexpositionsübungen in ihrem Alltag unterstützt. In einer ersten explorativen Machbarkeitsstudie wurde in einem Prä-Post-Design von zehn Personen qualitative Interviewdaten sowie quantitative Messungen erhoben. Die Nutzung sowie die Benutzerfreundlichkeit, Nutzerzufriedenheit und Akzeptanz der App wurden allgemein als hoch empfunden. In der auf die Machbarkeitsstudie folgenden Wirksamkeitsstudie wurden 92 Personen mit mild bis moderat ausgeprägten Panikbeschwerden in zwei parallele Gruppen randomisiert. Nach acht Wochen zeigte die Interventionsgruppe eine signifikante Verbesserung der Schwere der Paniksymptome im Vergleich zur Warte-Kontrollgruppe. Die Kovarianzanalyse mit den Baseline-Werten als Kovariate, ergab nach dem Intention-to-treat Ansatz einen mittleren Effekt von Cohen's d=0,66 in der Reduzierung der Panikbeschwerden zu Gunsten der Interventionsgruppe. Dieser Effekt stieg nach drei Monaten auf d=0,89 an und hielt sich zum 6- Monats Messzeitpunkt bei d=0,81. Auch Response- wie Remissionsraten waren bei der Interventionsgruppe signifikant höher. Dieser positive Effekt zeigte sich ebenfalls für sekundäre Endpunkte wie depressive Beschwerden und Lebensqualität. Ein Zusammenhang zwischen App-Nutzung und klinischen Zielkriterien konnte nicht gefunden werden. Mit dieser Arbeit konnte erstmals gezeigt werden, dass ein auf kognitiver Verhaltenstherapie beruhendes hybrides Online-Training zur Reduktion von Panikbeschwerden und Panikstörung wirksam ist. Zudem trägt diese Arbeit zu einem tieferen Verständnis des Potenzials mobiler Technologien im Feld E-Mental Health bei.
Entwicklung und Evaluation eines hybriden Online-Trainings bei Panikstörung und Agoraphobie
Keywords: 150 Psychologie